Navigation strategies as revealed by error patterns on the Magic Carpet test in children with cerebral palsy - Belmonti, Vittorio; Berthoz, Alain; Cioni, Giovanni; Fiori, Simona; Guzzetta, Andrea (Frontiers in Psychology, 2015)
Introduction Short-term memory develops differently in navigation vs. manual space. The Magic Carpet (MC) is a novel navigation test derived from the Walking Corsi Test and the manual Corsi Block-tapping Task (CBT). The MC requires mental rotations and executive function. In Cerebral Palsy (CP), CBT and MC scores relate differently to clinical and lesional factors. Hypotheses of this study are: that frontal lesions specifically affect navigation in CP; that brain lesions affect MC cognitive strategies. Material and methods Twenty-two children with spastic CP, aged 5 to 14 years, 14 with a unilateral and 8 with a bilateral form, underwent the CBT and the MC. Errors were classified into 7 patterns by a recently described algorithm. Brain lesions were quantified according to a novel semi-quantitative MRI scale. Control data were partially drawn from a previous study on 91 typically developing children. Results Children with CP performed worse than controls on both tests. Right hemispheric impairment correlated with spatial memory. MC span was reduced less than CBT span and was more selectively related to right middle white-matter and frontal lesions. Error patterns were differently distributed in CP than in typical development and depended on right brain impairment: children with more extensive right lesions made more positional than sequential errors. Discussion In CP, navigation is affected only by extensive lesions involving the right frontal lobe. In addition, these are associated with abnormal cognitive strategies. Whereas in typical development positional errors, preserving serial order, increase with age and performance, in CP they are associated with poorer performance and more extensive right-brain lesions. The explanation may lie in lesion side: right brain is crucial for mental rotations, necessary for spatial updating. Left-lateralized spatial memory strategies, relying on serial order, are not efficient if not accompanied by right-brain spatial functions.